Aplikasi Pengolahan Bantuan Sosial Berbasis Web dan Mobile di Kapanewon Kokap Kulon Progo - Nugroho, Muktiono; Wulandari, Sri (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The web and mobile-based social assistance processing application is designed to address issues in Kapanewon Kokap, Kulon Progo, which currently lacks an integrated web, mobile, and digital database application. As a result, the community must go to the Kapanewon office to apply for social assistance, which consumes time, energy, and costs due to the manual processes still in place, leading to slow service. To tackle this problem, the application is developed using the System Development Life Cycle (SDLC) prototype method, which allows for rapid development, low costs, and flexibility to user needs. The outcome of this application development facilitates the community in applying for social assistance quickly, accelerates administration, and enhances the transparency of aid distribution. With this application, the community no longer needs to visit the Kapanewon Kokap office, saving costs, time, and energy. In conclusion, this application improves the service process, provides better comfort for the community, and simplifies the online application process for social assistance, making the service more optimal and timely.